Self-energy device for HVDC breakers and its control strategy - Feng Xu; Yi Lu; Xiaohua Xuan; Haihong Yu; Peng Qiu; Daozhuo Jiang (The Journal of Engineering, 2019)
In order to reduce the cost of energy devices for IGBT drive circuits of the hybrid HVDC breaker, a self-energy device for the HVDC breaker is proposed here, which connects to DC lines and takes power from DC lines directly. The device consists of three operating modes: the start-up charging mode, the steady-state charging mode, and the maintenance restart charging mode. In view of these modes, corresponding control strategies are proposed to ensure the stability of power supply to drive circuits, and the simulation model is built and studied. For multi-terminal HVDC systems or HVDC grids, several self-energy devices in different lines can be connected through a certain combination, which can get the DC current flow regulation function.